PREDICTION MODEL FOR FATIGUE CRACK LENGTH UNDER REAL-TIME MEASURED SPECTRUM - ZHANG Chuan; CHEN YanHui (Jixie qiangdu)
In this paper,the crack propagation test was carried out under the real-time measured load spectrum for eight years. A metabolic model is constructed to predict crack length and the errors between the experimental results and the predicted results under different conditions is compared. The analysis results show that the model,combining with nondestructive testing techniques,could effectively predict crack length without fitting the material constants using a large number of tests. This model can also reduce the influence of load dispersion and material dispersion to prediction results,so that it greatly improves the reliability of prediction results. Moreover,this model can be applied to predict crack length in corrosion environment.